Quality-driven scheduling for long-term evolution system - Mohd. Ramli, Huda Adibah; Sandrasegaran, Kumbesan; Patachaianand, Rachod (Inderscience Enterprises Limited, 2011)
This paper proposes a novel packet scheduling algorithm that extends Opportunistic and Delay Sensitive (ODS) algorithm to simultaneously support Guaranteed Bit Rate (GBR) and Non-GBR (NGBR) services over downlink Long Term Evolution (LTE) system. The proposed algorithm utilises Channel Quality Information (CQI), average throughput, type of services, packet delay and buffer information when allocating and assigning the available Radio Resource Units (RRUs) among the users. It is demonstrated that the proposed algorithm is more efficient in terms of maximising throughput and simultaneously satisfying the Quality of Service (QoS) requirements of GBR and NGBR services at acceptable levels